Female mobility and bengali women’s travelogues in the nineteenth and early twentieth centuries - Harder, Hans (South Asia, 2020)
Pioneering women’s periodicals in Bengali in the second half of the nineteenth century eloquently deplore the social confinement of women. Contesting this paradigm of female immobility, travelogues written by Bengali women simultaneously start to appear in the pages of such journals as Bāmābodhinıī Patrikā, Bhāratıī, Antaḥpur, etc., from the 1860s onwards. Unlike the famous nineteenth-century Bengali travelogues by Krishnabhabini Das and Svarnakumari Debi, these other writings have only very recently drawn attention. After laying out the state of the art, I will first introduce two of the established travelogues. Thereafter I will look at these still largely unknown writings, measure their significance for a women’s public and the Bengali literary sphere, and evaluate their setting in terms of gender and class. Shorter and less spectacular, the accounts in these periodicals are nonetheless a significant body of literature. They furnish detailed insights into the travel conditions and social framework women in those days experienced, and amply bear witness to the literary sentiments travelling inspired.
Vol. 43, no. 5: Special issue mit eigenem Titel: Literary sentiments in the vernacular: gender and genre in modern South Asia
Gesehen am 17.02.2022